2022
DOI: 10.1371/journal.pone.0263372
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on risk factors for khat chewing among adolescents in the African continent and Arabian Peninsula

Abstract: Introduction Khat is a flowering plant with stimulant effect on the nervous system and produce psychological dependence. Despite its harmful effects, the ingestion of khat has been part of cultural norms and the legality of khat varies by region. Objective This systematic review aimed at critically evaluating the available evidence on the risk factors of khat chewing among adolescents. Methods A systematic review was conducted on published research studies from five databases Scopus, PubMed, Science-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The present study found higher odds of khat chewing among pregnant women who had a khat chewer partner than their counterparts. This association was also detected by previous studies (22,26), and might be due to the need for increasing intimacy and socialization with their partners (1). Similar to previous reports (32), the likelihood of khat chewing was higher among pregnant women with a history of pre-pregnancy khat chewing than among women without such a history.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The present study found higher odds of khat chewing among pregnant women who had a khat chewer partner than their counterparts. This association was also detected by previous studies (22,26), and might be due to the need for increasing intimacy and socialization with their partners (1). Similar to previous reports (32), the likelihood of khat chewing was higher among pregnant women with a history of pre-pregnancy khat chewing than among women without such a history.…”
Section: Discussionsupporting
confidence: 88%
“…Khat (Catha edulis) is an evergreen stimulant plant that is widely cultivated and consumed in East Africa and the Arabian Peninsula ( 1 ). The young buds and fresh, tender leaves are chewed to attain psycho-stimulation and euphoria ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, khat can be addictive, with those chewing it recognizing their dependence on the stimulant to complete everyday tasks [ 3 , 4 ]. Risk factors that increase one’s likelihood of chewing khat include identifying as male, having family members and peers who also chew khat, smoking frequently, having previous traumatic experiences, and living in either Oromia or Harar Regions in Ethiopia [ 3 , 5 , 6 ]. Those who use khat explain their use is primarily driven by its ability to increase concentration and to socialize with their friends and family [ 7 ].…”
Section: Introductionmentioning
confidence: 99%